The Effect of Industry Field Practice on the Work Readiness of Culinary Arts Students at Padang State University - Anati, Mutiara; Gusnita, Wiwik; Kasmita, Kasmita; Siregar, Juliana (Universitas Negeri Padang, 2025)
This study aims to determine the effect of industrial field practice on the job readiness of undergraduate students in the Family Welfare Education (Home Economics) Culinary Arts Program at Universitas Negeri Padang (UNP). The research employed a quantitative approach with a correlational method. The study was conducted at Universitas Negeri Padang, specifically involving students from the Family Welfare Education (PKK) program with a concentration in Culinary Arts. The population consisted of 189 students from the 2020–2022 cohorts, with a sample of 65 students selected using purposive sampling. The variables in this study included industrial field practice (X) as the independent variable and students’ job readiness (Y) as the dependent variable. The indicators of the industrial field practice variable (X) comprised work skills, practical experience, and problem-solving ability, while the indicators of the job readiness variable (Y) included skills, knowledge, understanding, and personality attributes. Data were collected using a Likert-scale questionnaire and analyzed through validity, reliability, and normality tests, as well as simple linear regression analysis. The results showed that industrial field practice had a significant effect on students’ job readiness, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.806. This means that 80.6% of the variation in students’ job readiness can be explained by industrial field practice, while the remaining 19.4% is influenced by other factors outside this study. These findings highlight that direct experience in the industrial field plays an important role in enhancing students’ skills, knowledge, understanding, and personality attributes as future professional workers in the field of culinary arts.